DESAIN APLIKASI INVENTARIS DAN PELESTARIAN MOTIF TENUN SONGKET KHAS JEMBRANA DENGAN MODEL PROTOTYPE - Ida Bagus Kade Dwi Suta Negara; I Putu Kusuma Negara (LPPM Universitas Dhyana Pura, 2021)
ABSTRACT The variety of Jembrana songket weaving motifs has been passed down from generation togeneration, and is usually created by certain and limited people. This is what causes the typicalJembrana songket weaving motif to be less well known by the general public. Only certain circles canrecognize the motifs of Jembrana's typical weaving. In addition, along with the rapid development oftechnological progress as it is today, people are starting to abandon the artistic and cultural valuesinherited by their ancestors, one of which is Jembrana's typical songket weaving. Many people are notfamiliar with Jembrana's typical songket weaving, especially the motifs. The method used in this studyis a software development method with a prototype model. In the prototype/prototyping model, theresulting software is then presented to the client, and the client is given the opportunity to provideinput and criticism, so that the resulting software is in accordance with the needs and desires of thecustomer. Software changes can be made many times until an agreement is reached on the form of thesoftware to be developed. The features provided in the inventory application design and preservationof Jembrana typical songket weaving motifs with this prototype model include: weaving motifinformation dashboard, weaving motif data management, motif narrative description management,and motif creator data management. Based on user evaluations that have been carried out, it showsthat the design of this application is good. However, with this system, users expect that the features ofthis application will be even more, such as the feature to display Jembrana's typical songket narrationin video form.Keywords: inventory, preservation, songket of jembrana.ABSTRAK Ragam motif tenun songket Jembrana telah diwariskan secara turun-temurun sejak dahulu, danbiasanya diciptakan oleh orang-orang tertentu saja dan terbatas. Hal tersebut yang menyebabkan motiftenun songket khas Jembrana kurang begitu dikenal oleh masyarakat awam. Hanya kalangan tertentusaja yang dapat mengenali motif dari tenun khas Jembrana. Disamping itu, seiring denganperkembangan kemajuan teknologi yang begitu pesat seperti saat ini, masyarakat mulai meninggalkannilai-nilai seni dan budaya yang diwariskan oleh para leluhur, salah satunya adalah tenun songket khasJembrana. Banyak masyarakat yang sudah tidak mengenal tenun songket khas Jembrana terutamamotifnya. Metode yang digunakan dalam penelitian ini adalah metode pengembangan perangkat lunakdengan model prototype. Dalam model prototype/prototyping, perangkat lunak yang dihasilkankemudian dipresentikan kepada klien, dan klien tersebut diberikan kesempatan untuk memberikanmasukan dan kritikan, sehingga software yang dihasilkan sesuai dengan kebutuhan dan keinginanpelanggan. Perubahan perangkat lunak dapat dilakukan berkali-kali hingga dicapai kesepakatan bentukdari software yang akan dikembangkan. Fitur yang disediakan dalam desain aplikasi inventaris danpelestarian motif tenun songket khas Jembrana dengan model prototype ini antara lain : dashboardinformasi motif tenun, manajemen data motif tenun, manajemen deskripsi narasi motif, danmanajemen data pencipta motif. Berdasarkan evaluasi pengguna yang telah dilakukan menunjukkanbahwa desain aplikasi yang dibuat ini sudah bagus. Namun dengan adanya sistem ini pengguna mengharapkan agar fitur-fitur dari aplikasi ini lebih banyak lagi, seperti misalkan fitur untukmenampilkan narasi songket khas Jembrana dalam bentuk video.Kata Kunci : inventaris, pelestarian, songket jembrana.